EVALUASI KURIKULUM ON GOING PGSD - ganes gunansyah (Universitas Sriwijaya, 2015)
Abstrack: The purpose of this research is to obtain information on the application of curriculum in force covering feasibility, practicality, and effectiveness of the curriculum, as well as data and information related to curriculum run, for decision making about the improvement in the level of the quality of implementation and to develop a curriculum that will come. This research uses descriptive method of evaluation. The design study is the CIPP evaluation model with taxonomy analysis and gap analysis study (study of the gap). Location of research conducted at the Department of PGSD, FIP UNESA. Respondents include active students began class of 2011 through 2014, the alumni program S1-PGSD start of 2007 to 2010, as well as users that school graduate Unesa PGSD partners. The results showed that there is still a discrepancy curriculum documents, responses of alumni or graduates. While user feedback graduates (stakeholders) regarding the implementation portion P3 through the practice of skills and experience is still insufficient to equip the participants, as well as still inadequate mastery of the English language skills. Keywords:curriculum evaluation, SNPT, KKNI. Abstrak: Tujuan penelitian ini untuk memperoleh informasi tentang penerapan kurikulum yang sedang berlaku yang meliputi keterlaksanaan, kepraktisan, dan keefektifan kurikulum, serta memperoleh data dan informasi terkait kurikulum yang dijalankan, untuk pengambilan keputusan tentang perbaikan dalam tataran kualitas pelaksanaan dan untuk pengembangan kurikulum yang akan datang. Penelitian ini menggunakan metode deskriptif evaluasi. Desain penelitian yang digunakan adalah model evaluasi CIPP dengan disertai analisis taxonomy dan analisis gap study (studi kesenjangan). Lokasi penelitian dilaksanakan di Jurusan PGSD, FIP UNESA. Responden penelitian meliputi mahasiswa aktif mulai angkatan 2011 sampai dengan 2014, alumni program S1-PGSD mulai angkatan 2007 hingga 2010, serta pengguna lulusan yaitu sekolah mitra PGSD Unesa. Hasil penelitian menunjukan bahwa masih terdapat ketidaksesuaian dokumen kurikulum, tanggapan alumni atau lulusan. Sementara tanggapan pengguna lulusan (stakeholder) mengenai porsi pelaksanaan P3 melalui praktek keterampilan dan pengalaman masih kurang cukup membekali peserta, serta masih kurang memadainya penguasaan terhadap kemampuan bahasa Inggris. Kata Kunci: evaluasi kurikulum, SNPT, KKNI.